THE BEGINNING OF ARTIFICIAL INTELLIGENCE (Web of Technology: Multidimensional Research Journal, 2024)
The article formulates the main goals and objectives of artificial intelligence. It is shown how AI is related to the development of world computer science. A brief history is also presented about the outstanding scientists who stood at the origins of cybernetics, computer science and artificial intelligence, as well as the prospects for its further development.